ANALISIS PENGELOLAAN SPECTRA MULTIMEDIA DI SMP NEGERI 1 BAGAN SINEMBAH KABUPATEN ROKAN HILIR (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThe aim of this study was to describe (1) the management of multimedia spectra (2) Utilization of multimedia spectra. (3) Maintenance multimedia spectra. This research is a qualitative study research approach phenomenological perspective. The study was conducted in SMP Negeri 1 Bagansinembah. Data collection technique used observation or documentation and interview. Data analysis with qualitative description of data reduction, data display and conclusion drawing / verification. The results are expected (1) the management of multimedia spectra into: needs, efficiency, excellence. In the process of multimedia learning spectra have been prepared by a team of creative multimedia spectra were acquired by the Education Department in Rokan Hilir and given to public schools after being given the training a few days, further developed by the Multimedia spectrayag school to be used by all the school teachers. With the help of multimedia spectra teachers are expected to improve the quality of uru creativity in the use of instructional media. (2) The use of multimedia spectra in the learning process has been adapted to the needs of learning. Making it easier for teachers to deliver learning in class, but if all teachers have a good understanding of the use of multimedia spectra. Is the number of multimedia spectra used in the implementation of learning sufficient. (3) Maintenance multimedia spectra carried out by teachers, laboratory assistants, and students continuously. Every minor damage to the multimedia spectra, carried out by the teacher. As for multimedia spectra with severe damage done by outsiders. Multimedia processing spectradilakukan continuous, periodic, and emergency.Keywords: learning media, planning, utilization, maintenance